Optimization of the Lens Nucleus Fragmentation during Phacoemulsification in Patients with Pseudoexfoliation Syndrome - V. M. Malov; A. V. Zolotarev; E. B. Eroshevskaya; I. V. Malov; A. E. Gorbunov (Oftalʹmologiâ, 2018)
Objective: Comparative analysis of the results of phacoemulsification (FEC) with the use of developed and classic technologies for fragmentation of the lens nucleus in patients with pseudoexfoliation syndrome (PES). Patients and methods. The proposed technology is gentle crushing of the lens nucleus in patients with PES, you can reduce the pressure on the fibers of the zonule, the probability of damage to the ligaments and posterior capsule of the lens based on the use of phacofragmentation original design. To determine the radius of curvature of the working part of the tool a morphometrical measurement of the curvature of the equatorial zone of the lens cores removed during extracapsular and intracapsular cataract extraction in patients with PEX subluxation of the lens was carried out. A comparative analysis of the operation and the results of surgical treatment of cataract in patients with PEX with the use of the proposed (n = 58) and standard (n = 56) technologies of the nucleus fragmentation in phacoemulsification was made. The following ultrasound parameters were estimated: the average capacity in % (AVEUS), the average values of the absolute time ultrasound (APT) and average values of effective (EPT) time of ultrasound, in seconds, during phacoemulsification; structural-morphological changes in the posterior epithelium of the cornea according to the endothelial microscopy; the frequency and nature of complications, the visual acuity. Results. Morphometry of the lens nuclei in patients with pseudoexfoliation syndrome allowed to determine the average radius of curvature of the nucleus equator, which is made up 2.89 ± 0.14 mm, according to the performance curve of the Gauss — 2.895– 3.530 mm. These data are taken into account when selecting the radius of curvature of the working part of phacofragmentation (the radius of curvature of 3.0 mm) used with FEC in patients with PES (Patent RU152761 from 25.05.2015). The proposed chopper due to the conformity of the working part curvature of the tool and the Equatorial zone of cataract kernel can reliably capture and grind it, thus eliminating excessive pressure on the ligaments of the crystalline lens in patients with PES. Developed technology contributes to significantly reduction of the energy performance of ultrasound: AVEUS — 2.64–10.00 %; APT — 3.38–14.00 %; EPT — on 3.76– 16.00 % by 6.76 % in patients with different of the lens nucleus density degree, decrease operative and postoperative complications twice, 1.5 times less cell loss back the corneal epithelium. Visual acuity without correction from the first days after surgery was higher than 0.5 (average of 0.70 ± 0.05) in all the patients and increased to an average of 0.91 ± 0.01 within 12 months in patients of the main and 0.85 ± 0.02 — control groups. Conclusion. The developed technology of fragmentation of the lens nucleus reduces the time of phacoemulsification, reduces the ultrasound load, causes a smaller loss of cells at the back of the corneal epithelium, reduces the possible complications of the iris and ciliary body, which increases the efficiency of surgical treatment of cataract in patients with PEX.